Patron Offending and Intoxication in Night- Time Entertainment Districts (POINTED). - Miller, P.; Pennay, A.; Droste, N.; Jenkinson, R.; Quinn, B.; Chikritzhs, T.; Tomsen, S.; Wadds, P.; Jones, S.; Palmer, D.; Barrie, L.; Lam, T.; et al. (Foundation for Alcohol Research & Education, 2014)
This book examines legislation on how alcohol is sold, promoted and consumed, and the implementation and enforcement of the regulations, from the perspective of reducing alcohol-related harm.